Heave and load-settlement behaviour of a chemically stabilised expansive clay bed. Issue 6 (2nd November 2022) - Ramanjaneya Raju, E.; Phanikumar, B. R.; Heeralal, M.
ABSTRACT: Structures found in expansive soils are subjected to heave and downward movement when they absorb water and lose water to the atmosphere, respectively. The upward and downward movements of structures built on the expansive clay strata are controlled through various treatment methods such as chemical stabilisation. As these clay strata are subjected to stresses due to superstructures, an understanding of their load-carrying capacity in the light of changing moisture content is required to assess this behaviour. This paper presents the heave and load-settlement behaviour of a remoulded expansive clay bed stabilised with varied amounts of lime, cement, fly ash and ground granulated blast furnace slag (GGBS). A series of laboratory-scale plate load tests were conducted on the beds of chemically stabilised clay compacted at the respective OMC and MDD. The plate load tests were conducted in two series: one on the as-compacted beds of the blends, and the other on the saturated beds of the blends to compare their stress-settlement behaviour. The amount of heave and the rate of heave were also monitored during the process of saturation. Chemically stabilised expansive clay beds reflected improved load-settlement behaviour in both the as-compacted and the saturated states.